Pengaruh E-Lkpd Berbasis Live Worksheet Tehadap Hasil Belajar Siswa Materi Sptldv Sman 1 Momunu - Musa, Febrianingsi A.; Usman, Kartin; Katili, Nancy (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
This study aims to investigate the influence of electronic worksheets based on live worksheets on student learning outcomes in the material of systems of linear inequalities with two variables. This research is an experimental study with research subjects classified into two groups: X-Gusdur class as the experimental group and X-ir. Soekarno, as the control group with the population, is SMA Negeri 1 Momunu, using a pre-test and post-test control group research design. Data collection techniques were test instruments based on indicators after the learning process. Pre-tests and post-tests were used to measure student learning outcomes. Data processing used descriptive analysis, showing that the average student learning outcomes in the experimental class were higher than in the control class. The results of the inferential analysis showed that both data were normally distributed and homogeneous; thus, the covariance analysis (ANACOVA) was continued, and results were obtained where Ho was rejected and Hâ‚ was confirmed.From the descriptive analysis, it can be seen that the average learning outcome score in the experimental group was 79.96, which was significantly higher than the average score in the control group, which only reached 69.19. Likewise, the results of hypothesis testing using the ANACOVA test also showed more favorable results for the experimental group with ð›¼ = 0.05 obtained by FcountFtable (12.024.04). Therefore, the research findings in heate that student learning outcomes are higher after being taught using ce on live worksheets than printed worksheets.